2023
DOI: 10.3390/microorganisms11030783
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Characterization of Phosphate-Solubilizing Bacteria from Tunisian Soils

Abstract: Soil microorganisms play an important role in maintaining natural ecological balance through active participation in carbon, nitrogen, sulfur, and phosphorous cycles. Phosphate-solubilizing bacteria (PSB) are of high importance in the rhizosphere, enhancing the solubilization of inorganic phosphorus complexes into soluble forms available for plant nutrition. The investigation of this species of bacteria is of major interest in agriculture, as they can be used as biofertilizers for crops. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…They were also dominant [50]. PSB species were isolated from Tunisian soils [50]. Other studies reviewed by Zhu et al [5] have also indicated that Pseudomonas is one of the most frequently isolated PSBs associated with different crops.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…They were also dominant [50]. PSB species were isolated from Tunisian soils [50]. Other studies reviewed by Zhu et al [5] have also indicated that Pseudomonas is one of the most frequently isolated PSBs associated with different crops.…”
Section: Discussionmentioning
confidence: 90%
“…Pseudomonas species were also the most frequently isolated PSBs from the rhizosphere of barley plants (9 out of the 17; 52.94%) [21], and the rhizosphere of shisham plants (7 out of 18 isolates; 38.89%) [49]. They were also dominant [50]. PSB species were isolated from Tunisian soils [50].…”
Section: Discussionmentioning
confidence: 99%
“…LB liquid alone was used as the control. The OD 600 values were measured and cell concentrations were adjusted to 1 × 10 7 CFU/mL (OD 600 = 1.0) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…P. fluorescens bacteria could increase soil P solubility and produce I.A.A. hormones [48]. In [49], it is concluded that Bacillus can dissolve P and K in large quantities.…”
Section: ) Corn Cob Weightmentioning
confidence: 99%